2022
DOI: 10.34659/eis.2022.81.2.462
|View full text |Cite
|
Sign up to set email alerts
|

Exemplifying the Zero Waste Concept in smart cities

Abstract: Due to the environmental imbalance on our planet, the concept of zero waste is gaining importance day by day. It is particularly important in the aspect of production and consumption cycle management and responsible waste management in urban space. The aim of this article is to exemplify methods of reducing waste in smart cities according to the author's Waste Management for Generation, Environment, and Gains (WM2GEG) scheme. An additional aim was to select the most effective ways of rational waste management … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…This, in turn, will influence the way the city's management is organised and the economic outcomes. Representatives of the different cities analysed in Jelonek and Walentek (2022) confirmed that creating plans to reduce waste in urban spaces and enforcing the positive behaviours and practices outlined in such a plan is a win-win solution for the ecosystem, residents and city budgets. A waste management programme should focus on increasing the role of the community in handling waste, not just adding equipment to collect rubbish (Nizar et al, 2018).…”
Section: Discussion/limitation and Future Researchmentioning
confidence: 82%
See 3 more Smart Citations
“…This, in turn, will influence the way the city's management is organised and the economic outcomes. Representatives of the different cities analysed in Jelonek and Walentek (2022) confirmed that creating plans to reduce waste in urban spaces and enforcing the positive behaviours and practices outlined in such a plan is a win-win solution for the ecosystem, residents and city budgets. A waste management programme should focus on increasing the role of the community in handling waste, not just adding equipment to collect rubbish (Nizar et al, 2018).…”
Section: Discussion/limitation and Future Researchmentioning
confidence: 82%
“…The use of modern waste management methods significantly increases the aesthetics of the city. This benefits the environment, society, and the budget of the territorial unit (Jelonek & Walentek, 2022).…”
Section: Discussion/limitation and Future Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…A greening activity is based on the principle of respect for the natural environment that takes into account the protection of the environment and the rational use of its resources with its simultaneous reproduction in the short term, preserving the potential of the environment (Jelonek & Walentek, 2022;Lavuri et al, 2021;Sukiennik et al, 2017). Any pro-environmental activity of an enterprise includes undertakings of the pre-and post-production and post-consumption phases (Lemkowska & Wiśniewska, 2022;Czyżewski et al, 2021), but due to the nature of the analyses carried out, this paper presents the actions taken during and in connection with the production process.…”
Section: An Overview Of the Literaturementioning
confidence: 99%